Identification of ATRNL1 and WNT9A as novel key genes and drug candidates in hypertrophic cardiomyopathy: integrative bioinformatics and experimental validation - He, Huabin; Liao, Yanhui; Chen, Yang; Qin, Hao; Hu, Longlong; Xiao, Shucai; Wang, Huijian; Yang, Renqiang (Frontiers in Molecular Biosciences, 2024)
Background: Hypertrophic cardiomyopathy (HCM) is a genetic disorder characterized by left ventricular hypertrophy, which can lead to heart failure, arrhythmias, and sudden cardiac death. Despite extensive research, the molecular mechanisms underlying HCM are not fully understood, and effective treatments remain limited. By leveraging bioinformatics and experimental validation, this study aims to identify key genes and pathways involved in HCM, uncover novel drug candidates, and provide new insights into its pathogenesis and potential therapeutic strategies.Methods: Commonly up-regulated and down-regulated genes in hypertrophic cardiomyopathy (HCM) were identified using GEO datasets, including three mRNA profiling datasets and one miRNA expression dataset. Enrichment analysis and hub-gene exploration were performed using interaction networks and consistent miRNA-mRNA matches. Potential drugs for HCM were screened. HCM cellular and animal models were established using isoproterenol. Key unstudied differentially expressed genes (DEGs) were validated. Animals were treated with novel potential drugs, and improvements in HCM were assessed via ultrasound metrics. Hematoxylin and eosin (H&E) staining was used to assess myocardial fibrosis. Immunohistochemistry was employed to detect differentially expressed genes in cellular experiments.We discovered 145 key up-regulated and 149 down-regulated DEGs associated with HCM development, among which there are 8 core up-regulated and 7 core down-regulated genes. There are 30 up-regulated and 6 down-regulated miRNAs. Between the 6 down-regulated miRNAs and 1291 matched miRNAs (against 8 core up-regulated DEGs), there is one common miRNA, miR-1469. Using the CTD database, drugs that impact the expression/abundance/methylation/metabolic process of core DEGs (after the exclusion of toxic drugs) included acetaminophen, propylthiouracil, methapyrilene, triptolide, tretinoin, etc. In the HCM cell model, only ATRNL1 and WNT9A were significantly increased. In the HCM animal model, propylthiouracil, miR-1469, and triptolide demonstrated therapeutic effects on HCM to varying degrees. And propylthiouracil, but not miR-1469 and triptolide, significantly inhibited the expression of ATRNL1 in the HCM model, and all of the three drugs suppressed WNT9A expression.In conclusion, we identified several novel genes in HCM development, among which ATRNL1 and WNT9A were validated by cell and animal models. A deficiency of hsa-miR-1469 may be a mechanism behind HCM development. Novel medications for HCM treatment include propylthiouracil and triptolide.